Burden and Characteristics of the Comorbidity Tuberculosis—Diabetes in Europe: TBnet Prevalence Survey and Case-Control Study. (19th December 2018) - Sane Schepisi, Monica; Navarra, Assunta; Altet Gomez, M Nieves; Dudnyk, Andrii; Dyrhol-Riise, Anne Margarita; Esteban, Jaime; Giorgetti, Pier Francesco; Gualano, Gina; Guglielmetti, Lorenzo; Heyckendorf, Jan; Kaluzhenina, Anna; Lange, Berit; et al.
Abstract: Background: The growing burden of diabetes mellitus (DM) is posing a threat to global tuberculosis (TB) control. DM triples the risk of developing TB, modifies the presenting features of pulmonary TB, and worsens TB treatment outcomes. We aimed to analyze the prevalence of DM among TB patients and to describe the characteristics and clinical presentation of TB-DM patients in Europe. Methods: We performed a cross-sectional survey on the prevalence of DM among consecutively diagnosed adult TB patients in 11 European TB referral centers located in France, Germany, Greece, Italy, Russia, Slovakia, Spain, and the United Kingdom over the period 2007–2015. We also selected DM-TB cases and TB only controls with a 1:3 ratio to perform a case-control analysis, including patients selected from the countries mentioned above plus Norway and Ukraine. Results: Among 3143 TB enrolled patients, DM prevalence overall was 10.7% and ranged from 4.4% in Greece to 28.5% in the United Kingdom. Patients' median ages ranged from 36 to 49 years, and all centers had >60% males; the proportion of foreign-born patients varied widely across sites. In the case-control study, DM was independently associated with older age and, among older patients, with being foreign-born. Among patients with pulmonary involvement, cavities on chest imaging were more frequently observed among those with DM. Conclusions: Diabetes mellitus represents a challenge for TB control in Europe, especially in foreign-born and in elderly patients. Specific screening strategies should be evaluated.